(untitled) (Theatrum historiae, 2010)
The Czechoslovakian exile government also needed to back up its political activity with military force. Therefore it attempted to built and strengthen Czechoslovakian foreign units, but there was a lack of human resources. Therefore the National Defence Ministry tried to find volunteers from the compatriotic minorities across the Atlantic, particularly in Canada and in the United States of America. Therefore, an army mission was planned and sent out to prepare and carry out a recruitment campaign. Their work was preceded by a few relatively long months of negotiations with the British and Canadian authorities in order to clarify what was wanted on all sides and to lay down the conditions for the work of the Czechoslovakian army mission in America.